2013
DOI: 10.1007/s10803-013-1757-3
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Difficulty in Understanding Social Acting (But Not False Beliefs) Mediates the Link Between Autistic Traits and Ingroup Relationships

Abstract: Why do individuals with more autistic traits experience social difficulties? Here we examined the hypothesis that these difficulties stem in part from a challenge in understanding social acting, the prosocial pretense that adults routinely produce to maintain positive relationships with their ingroup. In Study 1, we developed a self-administered test of social-acting understanding: participants read stories in which a character engaged in social acting and rated the appropriateness of the character’s response.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…However, they are delayed in using information about innocent intentions to forgive accidents (18). Furthermore, even very high-functioning adults with ASD who pass traditional tests of understanding (false) beliefs neglect beliefs and intentions in their moral judgments compared with NT adults (19,20). In the current sample, this effect was observed more strongly in z-scored behavioral data (SI Behavioral Results: Raw Behavioral Responses, Group Comparison) (21).…”
Section: Pattern Discrimination Of Intentional Vs Accidental Harm Ismentioning
confidence: 63%
See 1 more Smart Citation
“…However, they are delayed in using information about innocent intentions to forgive accidents (18). Furthermore, even very high-functioning adults with ASD who pass traditional tests of understanding (false) beliefs neglect beliefs and intentions in their moral judgments compared with NT adults (19,20). In the current sample, this effect was observed more strongly in z-scored behavioral data (SI Behavioral Results: Raw Behavioral Responses, Group Comparison) (21).…”
Section: Pattern Discrimination Of Intentional Vs Accidental Harm Ismentioning
confidence: 63%
“…These moral judgments depend on individuals' ability to consider another person's beliefs, intentions, and knowledge, and emerge relatively late in childhood, around age 6-7 y (15). Individuals with autism spectrum disorders (ASD), who are disproportionately impaired on tasks that require them to consider people's beliefs and intentions (16,17), are also impaired in using information about an innocent intention to forgive someone for accidentally causing harm (18)(19)(20), but see ref. 21).…”
mentioning
confidence: 99%
“…This same capacity may also be critical in everyday cooperative situations, however. According to a recent hypothesis (Baillargeon et al, 2013; Yang & Baillargeon, 2013), one important function of our abstract ability to represent false beliefs, pretense, and other counterfactual mental states is that it makes possible social acting , the well-intentioned social pretense we routinely produce in the form of white lies, tactful omissions, feigned interest, hidden disappointments, and false cheer. Social acting helps to maintain positivity within groups: it prevents aggressive confrontations, avoids hurt or embarrassed feelings, smoothes over awkward situations, and bolsters feelings of trust and acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent gaze-cueing task, only those with low AQ scores were found to have learned this information as reflected by their speeded responses, whereas those with high AQ scores showed no evidence of learning the characters’ dispositions; the authors attributed this to impairment in implicit learning. In another study, Yang and Baillargeon (2013) found that participants with more autistic traits performed less well in a novel social task involving rating the appropriateness of a character’s responses.…”
Section: Introductionmentioning
confidence: 99%